Correction to: Guidelines for Neuroprognostication in Adults with Guillain–Barré Syndrome (Neurocritical Care, (2023), 10.1007/s12028-023-01707-3) - Busl, Katharina M.; Fried, Herbert; Muehlschlegel, Susanne; Wartenberg, Katja E.; Rajajee, Venkatakrishna; Alexander, Sheila A.; Creutzfeldt, Claire J.; Fontaine, Gabriel V.; Hocker, Sara E.; Hwang, David Y.; Kim, Keri S.; Madzar, Dominik; et al. (Neurocritical Care, 2023)
The original article has been updated to correct Row 2 of Table 4 “04-Jul” to “4–7”.
CRIS-Team Scopus Importer:2023-05-05